Two case reports: Pica as a persistent eating disorder associated with iron deficiency anaemia - Azan A Nyundo; Godfrey Mwasada; Bonaventura C.T Mpondo (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Introduction: Pica is a mysterious condition characterised by patients developing cravings for non- nutritive substances that may escalate into serious medical complications. We present two case reports with a somewhat unusual nature of presentation attributed to iron deficiency. The first is a 25-year old African woman with abnormal uterine bleeding presenting with a fondness for eating clay, cold drinks, and icepacks. The second is 15- year old African girl who presented with bleeding from the nose, habitual smelling of soil, consuming ice packs and chewing rubber bands. Both presented with haematological parameters diagnostic of iron deficiency anaemia. Conclusion: Despite being practised for centuries, the clinical significance of pica symptoms is often not recognised particularly among the younger physicians. Both our patients responded well to managing the primary cause of blood loss and iron supplementation. We are convinced that pica is an important pointer to iron deficiency and clinicians should suspect occult blood loss in a patient presenting with pica symptoms.